Asimetri Kepatuhan Dalam Sistem Self-Assessment: Analisis Yuridis Atas Perampasan Aset Non-Pemidanaan Dan Mandatory Disclosure Rules Di Indonesia - Lina, Angie Angel; Theresia, Maria; Affrilies, Marlia Hafny; Fajri, Pujangga Candrawijayaning (Universitas Harapan Bangsa, 2025)
The self-assessment tax system in Indonesia, which gives full responsibility to Taxpayers (WP), serves as the main pillar of state revenue. Although annual tax revenue achievements are quite good, there is a compliance gap marked by a low tax ratio and room for opportunistic behavior. This study analyzes the existing tax legal framework, including the KUP Law, the TPPU Law, and regulations related to information exchange (AEoI) and beneficial ownership, to assess their effectiveness in preventing and prosecuting tax avoidance and tax evasion. This research uses a normative legal research method and a statute approach. The results of this study show that the legal instruments currently in force are not yet fully adequate to address complex tax avoidance schemes. This study proposes Non-Conviction Based (NCB) Asset Forfeiture and Mandatory Disclosure Rules (MDR) as complementary compliance architecture for novelty proposals. NCB Asset Forfeiture can accelerate the recovery of state losses without relying on criminal decisions that have permanent legal force, while MDR will encourage early reporting of aggressive tax planning schemes by intermediaries. This proposal is expected to sustainably strengthen the state's fiscal capacity, narrow the gap between norms and practice, and close law enforcement gaps in the Indonesian tax system.